2017
DOI: 10.1002/ejp.1138
|View full text |Cite
|
Sign up to set email alerts
|

Are you better? A multi‐centre study of patient‐defined recovery from Complex Regional Pain Syndrome

Abstract: Those with longstanding CRPS may no longer meet diagnostic criteria but still be symptomatic. Defining recovery is therefore problematic in CRPS. Our study has identified patients' definition of recovery from CRPS, in order of priority, as relief from: their CRPS-related pain, generalised pain, movement restriction, reliance on medication, and stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 55 publications
0
20
0
3
Order By: Relevance
“…Other studies [12,16] assessing pain and severity scores confirmed that pain remained present in the long term showed that CRPS patients consider themselves recovered when they were relieved from local or generalized pain and discomfort. For the majority, CRPS resolves within a year, but prospective studies have indicated severe pain remaining in 13% of the patients at one year or more after the diagnosis [59].…”
Section: Crps Severity Scorementioning
confidence: 94%
See 3 more Smart Citations
“…Other studies [12,16] assessing pain and severity scores confirmed that pain remained present in the long term showed that CRPS patients consider themselves recovered when they were relieved from local or generalized pain and discomfort. For the majority, CRPS resolves within a year, but prospective studies have indicated severe pain remaining in 13% of the patients at one year or more after the diagnosis [59].…”
Section: Crps Severity Scorementioning
confidence: 94%
“…Llewellyn et al [12] reported on 242 chronic CRPS that muscle weakness and decreased range of motion were the most frequent symptoms. These findings underlined the importance to improve motor function and reduce stiffness as priorities in rehabilitation.…”
Section: Strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…A change between RS2 (immediately before the commencement of treatment) and RS3 (immediately after the end of the treatment period) in current self-reported pain intensity and CRPS severity score [35,52] are the primary outcomes. People with CRPS consider pain relief to be the highest priority for recovery [59], and pain intensity is the most common primary outcome in chronic pain trials [60]. Current pain intensity is measured using item 6 of the Brief Pain Inventory (BPI; short form) [42], which is a Numerical Rating Scale (NRS) ranging from 0 -"no pain" to 10 -"pain as bad as you can imagine".…”
Section: Primary Outcomesmentioning
confidence: 99%